Experimental and analytical study of invisible water leaks detection using ground penetrating radar - Lee, Le Ming, 1989-, author; Mazlan Hashim, 1961-, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Project Paper (Sarjana Muda Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2014